MRSA infection in vascular surgical patients: The HKL experience - Wong HS,; William Chan YH,; Neeta KB,; Lum SG,; Seet KC,; Tan HL,; Naresh G,; Zainal Azizi A,; Ismail S, (Penerbit UKM, 2008)
Methicillin-resistant Staphylococcus aureus (MRSA) infection is important among vas-cular surgical patients. Its effect can be devastating resulting in limb amputation and mortality. We performed a retrospective patients record analysis to determine the pat-tern of MRSA infection among vascular surgical patients in Hospital Kuala Lumpur from January 2005 to December 2007. We also attempted to identify the factors asso-ciated with poor clinical outcome after such infection. There were 999 patients who underwent vascular surgeries in HKL within the analysis period. Of these 24 patients (2.4%) were detected to have MRSA surgical site infection. The infection was commoner among cigarette smokers, patients with diabetes melitus and those who had previous vascular surgery. Most infections occurred in the emergency surgery category and manifested as wound breakdown. Fifty-four percent of the infected pa-tients ended with graft removal, amputations or death. MRSA infection complicating vascular surgery resulted in poor clinical outcome. This serious threat requires intensi-fied preventive measures